PARTISIPASI PEREMPUAN RUMAH TANGGA NELAYAN DALAM SEKTOR USAHA MIKRO, KECIL DAN MENENGAH DI WILAYAH PESISIR TELUK KENDARI - Sumiyadi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
The aim of this study was to find out: Specifically the profile of women fishermenhouseholds in the coastal areas of Kendari Bay, West Kendari Subdistrict and to findout the impact of involvement of fishermen household women in the MSME sector(Micro, Small and Medium Enterprises) in the Kendari Bay Kendari District West. Thisstudy uses qualitative data as for the method used in this study is to use the method ofobservation, interviews / interviews, documentation and literature. While the dataanalysis technique uses data reduction methods, data display and data verification.From the results of this study it can be concluded that the lowest level of formal education of female fishermen households has only finished primary school, making thechoice of participation of respondents to work in the informal sector of Micro, Small andMedium Enterprises / MSMEs. Respondents who work in the MSME sector are themajority of the productive age group between the ages of 35 - 39 years. Although thereis no empowerment program in the form of entrepreneurship training from both theGovernment and Stakeholders, the respondents can be "self-empowered" due to theaccessibility of facilities and infrastructure that are easy and sufficient to support theireconomic activities. Respondent participation in the MSME sector because of thefamily's economic condition from the livelihood provided by the husband is still veryminimal to meet basic needs. With the participation of respondents working in theinformal MSME sector, it has increased family income. The increase in family incomehas a positive impact on the ability to fulfill basic needs of fishermen households in thecoastal areas of Kendari Bay, West Kendari sub-district